Sistem Pendukung Keputusan Pemilihan Program Studi Bagi Calon Mahasiswa Baru Pada Universitas Proklamasi 45 Yogyakarta Menggunakan Metode Analytical Hierarchy Process - Johan Pursaka; Hendri Hendri (Journal Of Information System And Artificial Intelligence, 2023)
Determining the choice of a study program to continue their studies in higher education for some people is not easy, in addition to what criteria must be used as benchmarks as well as information about costs, what facilities are provided, what infrastructure supports lecture activities are also basic things that must be considered. not so well known by many prospective students. In determining the criteria that become the benchmark for assessment, people who know or are termed experts, the problem is if the choice of the designated study program is not in accordance with the characteristics of prospective students, it will be a separate obstacle in completing future studies. This study discusses the process of selecting a study program for prospective new students using the Analytical Hierarchy Process (AHP) method based on the most commonly used criteria such as costs, accreditation and facilities, which will be compared with all study programs at Proklamasi 45 University Yogyakarta. The results showed that the most recommended information engineering study program with a total weight of 0.1389 or 13.9% followed below that of mechanical engineering and industrial engineering with a total weight of 0.1367 or 13.7% and 0.1202 or 12, respectively. 0%.